PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sigit Cahyono; Ni Ketut Surasni; Hermanto Hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
This research aims to analyze the effect profitability to firm value with capital structure as moderating variable in agriculture companies listed on the Indonesia Stock Exchange (IDX). The dependent variable used is firm value (PBV), the independent variable is profitability (ROA), and capital structure (DER) as a moderating variable. The sampling technique was purposive sampling so that the number of samples obtained was 9 companies, with an observation period of 2014-2017. This type of research is associative causal. The analysis technique used in this study is panel date regression (common effect modell) using eviews, with a significant level of 5 percent. Descriptive statistics were also included which included average, median, minimum, maximum, and std. deviation. The results of this study indicate that profitability has a positive and significant effect on firm value and, capital structure is weaken on the relationship of profitability to firm value. Capital structure is a quasi moderating where as the effect of capital structure to firm’s value and the effect of capital structure interaction to firm’s value is also significant.Keywords: Profitability, Capital Structure, Firm Value